Assessing coach motivation: The development of the coach motivation questionnaire (CMQ) - McLean, K. N.; Mallett, C. J.; Newcombe, P. (Journal of Sport & Exercise Psychology, 2012)
The aim of this research was to develop and assess the psychometric properties of the Coach Motivation Questionnaire (CMQ). Study 1 focused on the compilation and pilot testing of potential questionnaire items. Consistent with self-determination theory, items were devised to tap into six forms of motivation: amotivation, external regulation, introjected regulation, identified regulation, integrated regulation, and intrinsic motivation. The purpose of the second study (N = 556) was to empirically examine the psychometric properties of the CMQ. Items were subjected to confirmatory factor analyses to determine the fit of the a priori model. In addition, the validity of the questionnaire was assessed through links with the theoretically related concepts of intrinsic need satisfaction, well-being, and goal orientation. Together with test-retest reliability (Study 3), these results showed preliminary support for the psychometric properties of the CMQ. Finally, using an independent sample (N = 254), the fourth study confirmed the factor structure and supports the use of the CMQ in future coaching research.